Improving Students' Mathematics Learning Outcomes with the Geogebra Assisted Active Index Card Match Method at the Third Grade SMP Negeri 3 Kolaka - Evi Safitri; Andi Mariani Ramlan; Arbain Arbain; Fitriyani Hali (JME (Journal of Mathematics Education), 2020)
The aim of the study was to improve the learning outcomes of Mathematics through the Geogebra-assisted Active Index Card Match method for students in class VIIIC of SMP Negeri 3 Kolaka. This type of research is classroom-based action research that is conducted collaboratively between teachers, observers, and researchers with research procedures that include planning, implementation, observation, and reflection. The type of data obtained are quantitative data from the results of learning tests and qualitative data through observation sheets. This research was conducted at SMP Negeri 3 Kolaka from 2 to 28 May 2019 in class VIIIC with a total of 26 students. The results of the study refer to the Minimum Completeness Criteria (KKM), that is, 80% of the students obtained a score of 68. The average score of the initial test results is 49.67. After the evaluation of the first cycle of action, the classic completeness reaches 50.00% (mean value 67.12%). This means that the first cycle of action increased from the daily test results of students. According to the results of the second cycle of action tests, the classic completeness was 80.77% (the average value was 76.30). It can therefore be concluded that the Geogebra Active Index Card Match assisted learning method can improve the learning outcomes of Mathematics for the students of class VIIIC of SMP Negeri 3 Kolaka.